Characterizing the neurocognitive profiles of children with moyamoya disease using the Das Naglieri cognitive assessment system - Kusano, Yusuke; Funaki, Takeshi; Ueda, Keita; Nishida, Noyuri; Tanaka, Kanade; Miyamoto, Susumu; Matsuda, Shuichi (Scientific reports, 2022)
Although cognitive impairment is well-documented in children with moyamoya disease (MMD), selective decline in specific neurocognitive domains remains controversial. The purpose of this study was to characterize the neurocognitive profile of children with MMD using the Das Naglieri Cognitive Assessment System (CAS) and the Wechsler Intelligence Scale for Children, Fourth Edition (WISC-IV). We analyzed the neurocognitive data of 30 children (median age, 7 years) with MMD who were assessed with the CAS and the WISC-IV before surgery. We focused on the comparison of standard scores and intraindividual differences across domains. The CAS scores significantly varied across four measures (standard scores, p < 0.001; intraindividual differences, p < 0.001). Post-hoc analyses revealed that the standard scores and intraindividual differences for successive processing were significantly lower than those for planning and attention. The WISC-IV scores did not significantly vary among the four measures, although the working memory index was the lowest among the four measures. The within-individual weakness in successive processing, a form of working memory function, may be a distinct characteristic of children with MMD. The CAS may be more sensitive than the WISC-IV for detecting this selective neurocognitive weakness in children with MMD.